2021
DOI: 10.1016/j.jclinepi.2021.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics data complemented drug use information in epidemiological databases: pilot study of potential kidney donors

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Blood was drawn on the day of the study visit after a fasting period of 8 to 12 h. Urine was collected by participants starting 24 h prior to the study visit, following strict instructions as previously described in detail [ 28 ]. Urinary boron concentrations were determined using inductively coupled plasma mass spectrometry (ICP-MS), as summarized in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was drawn on the day of the study visit after a fasting period of 8 to 12 h. Urine was collected by participants starting 24 h prior to the study visit, following strict instructions as previously described in detail [ 28 ]. Urinary boron concentrations were determined using inductively coupled plasma mass spectrometry (ICP-MS), as summarized in Supplementary Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding medicine, metabolomics can be useful to identify the mode of action of new drugs by analyzing biochemical pathways and, in conjunction with complementary assays, identify therapeutic potential [ 18 ]. It can also be applied to understand how diseases and/or health problems act on organisms, the effects of drug use, and drug development and to identify responsible biomarkers [ 19 ]. It is important to note that the information generated through research contributes to the complementation of medicine and related areas; epidemiological databases are just one example [ 19 ].…”
Section: Metabolomic Studiesmentioning
confidence: 99%
“…It can also be applied to understand how diseases and/or health problems act on organisms, the effects of drug use, and drug development and to identify responsible biomarkers [ 19 ]. It is important to note that the information generated through research contributes to the complementation of medicine and related areas; epidemiological databases are just one example [ 19 ].…”
Section: Metabolomic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, non-targeted metabolomics, designed for the broad characterization of ideally all relevant small molecules in a biological sample, can help to answer the question of how well self-reported and blood-detected drug uses match. Indeed, a pilot study conducted on 83 subjects deployed metabolomics to test whether questionnaire-derived medication use could be verified using metabolomics readouts from urine [ 18 ]. The study showed that molecular evidence for many classes of medication could be obtained from urine metabolic profiles.…”
Section: Introductionmentioning
confidence: 99%